PENGARUH SOSIALISASI TENTANG PENCEGAHAN VENTILATOR ASSOCIATED PNEUMONIA (VAP) TERHADAP PENGETAHUAN DAN PERILAKU PERAWAT RUANG INTENSIVE RS ” X ” TANGERANG TAHUN 2017 - Erliana Tresnadewi; Dewi Anggraini (STIKes IMC Bintaro, 2018)
Introduction : Pneumonia that accurs 48 hours or more after the use of a mechanical ventilator is Ventilator Associated Pneumonia (VAP), which presents nosocomial infections commonly encountered in the intensive care unit. Knowledge that must be owned by a nurse in the intensive unit such as airway management, including also the use of mechanical ventilator which often cause problems such as lung infections such as pneumonia. Research objectives : To analize the effect of socialization on prevention of VAP to knowledge and behavior of intensive space nurses. Research Methodology : This type of research using Pre-Experiment design with selected design is One group pretest posttest design. Sampling technique in total sampling, that is as much as 42 respondents. Data analysis was performed using T dependent test and wilcoxon test with 95% confidence interval and value α = 0,05. Research result : Mean of knowledge pre socialization 77,26 (SD 9,187) and post socialization 90,60 (SD 8,710). Mean of behavior pre socialization 74,64 (SD 8,582) and post socialization 87,98 (SD 8,342). The result obtained indicate a different level of knowledge between pre and post socialization about prevention Ventilator Associated Pneumonia (p value = 0,000; α 0,05) and there are differences in nurse behavior between pre and post socialization about prevention Ventilator Associated Pneumonia (p value = 0,000; α 0,05). Conclusion : There is the influence of socialization on the prevention of ventilator associated pneumonia (VAP) to knowledge and behavior of intensive care nurse.